Analisis Vegetasi Herba di Dusun Malempo Resort Mallawa Taman Nasional Bantimurung Bulusaraung Kabupaten Maros - Alim, Nurmaranti Alim; Utami Zainuddin, Dian (Pangale Journal of Forestry and Environment, 2023)
This research is to identify the composition and the structure of herbs vegetation, as well as the relation between environmental factor and the vegetation structure on Backwood in Malempo, Resort Mallawa of Bantimurung Bulusaraung National Park, District of Maros. It is located in three wind directions are South, North and West. This setting of the transect is alternatingly made at each of wind direction by five times. In every transect with the measurement of 20m x 2m there are 10 plots for herbs each plot is 2m x 2m and alternatingly placed. The collecting of vegetation data is made in the plot by counting the individual quantity of every species of herbs the determine the extent of the canopy. Herbaceous species found in Malempo Resort Mallawa TN. Babul, as many as 18 families and 43 species. The composition and structure of herbaceous species has a negative relationship with the height and percentage of land that is not overgrown with vegetation, while it is positively related to soil temperature.